Implementasi Metode Simple Additive Weighting (SAW) Pada Sistem Pendukung Keputusan Pemilihan Jenis E-Wallet - Ady Gilang Firmasyah; Irfan Muflih Amirullah; Siti Nurhalizah; Yuwan Jumaryadi (INTECH, 2024)
In an era where cash transactions are being replaced by digital transactions, users are faced with a dilemma between the many choices of e-wallet types. This choice challenges users to have to align their preferences and needs with the available digital transaction methods. This research aims to develop a decision support system based on Simple Additive Weighting (SAW) to assist users in evaluating their level of suitability for digital payment methods. The SAW method is used to assess important aspects such as ease of use, security, costs, and availability of both types of transactions. Each aspect is given weight according to its significance in decision making. The results of this research provide detailed guidance to users in considering their preferences and needs regarding digital transaction methods. By using a SAW-based decision support system, users can make more appropriate decisions according to their needs. The development of this decision support system is an important step in assisting users in evaluating and selecting various types of e-wallets.